Penguatan Kapasitas Berpikir Kritis Siswa SD Negeri 1 Pliken melalui Pendekatan Reading Aloud - Hafizhah, Hasna; Wakhudin, Wakhudin (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2026)
This study aimed to evaluate the effectiveness of the read-aloud strategy in strengthening the critical thinking skills of fifth-grade students at SD Negeri 1 Pliken, Banyumas. This study employed a qualitative approach using a case study design. Data were collected through participant observation, semi-structured interviews involving one instructor and five selected students as participants, and documentation to support the validity of the findings. Data analysis followed the interactive model proposed by Miles, Huberman, and Saldaña. The results showed that the implementation of reading aloud occurred in three distinct phases: pre-reading, reading execution, and post-reading. The impact was identified in three aspects of critical thinking. First, interpretation: students were able to understand explicit and implicit meanings, retell the story in their own words, and identify moral messages. Second, analysis: students were able to explain cause-and-effect relationships, distinguish between important and unimportant parts, and identify parts that made sense. Third, evaluation: students are able to assess the truthfulness of the story’s content, provide logical arguments, and relate it to everyday life. Supporting factors include the teacher’s ability to read expressively and facilitate interactive discussions. Hindering factors include differences in students’ initial abilities and time constraints.